On the multiple frontiers of extraction: excavating contemporary capitalism. Issue 2 (4th May 2017) - Mezzadra, Sandro; Neilson, Brett
ABSTRACT: Understanding the intensification and expansion of extractive industries in contemporary capitalism requires an approach attentive not only to the literal forms of extraction prevalent in mining and agribusiness but also to new fronts of extraction emerging in activities such as data mining and biocapitalism. This article introduces the concept of operations of capital to trace connections between the expansive logic of extraction and capitalist activity in the domains of logistics and finance. Arguing that extractive operations are at large across these domains, we explore their relevance for capital's relation with its multiple outsides. The resulting analysis provides a basis for mapping struggles against the changing forms of dispossession and exploitation enabled by extraction.